2008
DOI: 10.26522/br.v10i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Earthways: Opportunity, Community and Meaning in the Personal Garden

Abstract: The hybrid space of the personal garden offers valuable opportunities for individuals to express themselves personally in an outdoor setting, to develop meaningful relationships with green spaces, and to connect with the greater natural environment and urban community, as demonstrated in the works of contemporary gardener-authors Marjorie Harris, Sara Stein, and Leon Whiteson. These opportunities are particularly significant in urban environments where access to nature and green space is limited, and where gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many pro-environmental behaviors take place if the infrastructural supports are provided [20]. Some of these infrastructural supports that might influence UA participation include access to land, water, seeds, fertilizers, pesticides, herbicides, tools, gardening supply stores [15,36], urban planning regulations and building codes [37], land tenure laws [38], as well as the presence of a local market which stocks agricultural products [39]. In the United States, Inkoom [40] found a positive link between subsidies and the level of organic adoption among farmers during the transitioning phase in the United States.…”
Section: Infrastructural Factorsmentioning
confidence: 99%
“…Many pro-environmental behaviors take place if the infrastructural supports are provided [20]. Some of these infrastructural supports that might influence UA participation include access to land, water, seeds, fertilizers, pesticides, herbicides, tools, gardening supply stores [15,36], urban planning regulations and building codes [37], land tenure laws [38], as well as the presence of a local market which stocks agricultural products [39]. In the United States, Inkoom [40] found a positive link between subsidies and the level of organic adoption among farmers during the transitioning phase in the United States.…”
Section: Infrastructural Factorsmentioning
confidence: 99%
“…Other reports and research publications have identified factors that influence participation in urban edible gardening on a more theoretical basis, making claims without citing quantitative empirical evidence (Drescher, 1999;Nugent, 2000;Sander-Regier, 2008). For example, Drescher (1999) (Drescher, 1999).…”
Section: Factors Which Influence Participation In Edible Gardeningmentioning
confidence: 99%